Evaluation of microbial and physico-chemical qualities of some cough syrups marketed in Sana'a city, Yemen. - Ali G. Al−Kaf; Saeed M. Alghalibi; Wadhah H. Edrees (GarVal Editorial Ltda., 2015)
Context: Microbial contamination of cough syrups can bring clinical hazards to the users or patients as well as physical and chemical changes in the product. Aims: To evaluate the microbial and physicochemical characteristics of two hundred samples of four different types of cough syrups marketed in Sana'a city, Yemen. Methods: All collected samples were subjected to the following examinations: the total microbial count, type of isolated microorganisms, physical parameters, and concentration of active ingredients were identified and assessed by standard techniques described in US Pharmacopeia. Results: All the cough syrup samples used contained viable microbial load within acceptable limit according Pharmacopeia specifications. Bacillus subtilis, Micrococcus fulvum, and Staphylococcus epidermidis were the most commonly recovered bacteria. However, Aspergillus niger, Aspergillus fumigatus, Penicillium notatum, Mucor sp., and Aspergillus flavus were the most fungi isolated. The physical properties represented in the appearance, density, and pH of the analyzed samples complied with Pharmacopoeia standards. The concentrations of diphenhydramine HCl (92,51 - 108,78%), pseudoephedrine HCl (94,55 - 109,07%), and triprolidine HCl (98,20 - 104,19%) were recorded. Conclusions: All cough syrups marketed in Sana'a City had good microbiological and physico-chemical qualities.